2017
DOI: 10.1016/j.idcr.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

A case of Klebsiella oxytoca endocarditis in an intravenous drug user

Abstract: Non-HACEK Gram-negative bacilli account for only a small percentage of infective endocarditis cases globally. Among those, Klebsiella species account for only about 10% of cases and are most often health-care acquired. We present a rare case of Klebsiella oxytoca endocarditis in a young intravenous drug user.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This patient received a combination of imipenem, sulbactam, gentamycin and tigecycline with a good evolution, being referred to surgery after the correction of AG. There are several cases in the literature with IE caused by Klebsiella pneumonia and Klebsiella oxitoca in intravenous drug addicted [29][30][31] and hemodialysis patients 32 . Also, two cases of nosocomial IE in adults and children caused by ESBL-producing Klebsiella pneumoniae have been reported 33-34.…”
Section: Discussionmentioning
confidence: 99%
“…This patient received a combination of imipenem, sulbactam, gentamycin and tigecycline with a good evolution, being referred to surgery after the correction of AG. There are several cases in the literature with IE caused by Klebsiella pneumonia and Klebsiella oxitoca in intravenous drug addicted [29][30][31] and hemodialysis patients 32 . Also, two cases of nosocomial IE in adults and children caused by ESBL-producing Klebsiella pneumoniae have been reported 33-34.…”
Section: Discussionmentioning
confidence: 99%
“…Klebsiella oxytoca endocarditis is extremely rare. Only 10 other cases have been reported in the literature ( Table 1 ) [ 3 12 ]. They are usually found in immunocompromised patients, with a biliary, urinary, cutaneous, and sometimes peritoneal portal [ 5 ], and associated with high morbidity and mortality compared to other gram-negative bacillus endocarditis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous European studies have shown that Klebsiella pneumoniae and E. coli were the species most frequently responsible for ESBL secretion [3], especially K. pneumoniae, part of the natural intestinal microflora, but regarded as an opportunistic pathogen [4,5]. The colonization of biological tissues by K. pneumoniae frequently causes a large variety of diseases [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%